2013
DOI: 10.1159/000346525
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Treatment for Chronic Lung Diseases

Abstract: Chronic lung diseases such as idiopathic pulmonary fibrosis and cystic fibrosis or chronic obstructive pulmonary disease and asthma are leading causes of morbidity and mortality worldwide with a considerable human, societal and financial burden. In view of the current disappointing status of available pharmaceutical agents, there is an urgent need for alternative more effective therapeutic approaches that will not only help to relieve patient symptoms but will also affect the natural course of the respective d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 98 publications
2
24
0
Order By: Relevance
“…Importantly, we identified SOD1 by an MS approach as a paracrine factor that is secreted by aortic and BM-MSCs, but in particularly high amounts by AoMSCs. This corroborates the general view that engraftment in the lung is currently not considered the main mechanism by which MSCs repair a diseased lung tissue (36,78). Consistently we detected only a few, preferably single donor cells in WTI lung sections while circulating enhanced green fluorescent protein [EGFP(+)] MSCs could be detected in peripheral blood even 25 weeks after transplantation, supporting the idea that tissue protection is due to paracrine signaling (44).…”
Section: Murine Wt Bm (Xrt/bm) Cells From C57bl/6 Donor Mice Into Thesupporting
confidence: 89%
“…Importantly, we identified SOD1 by an MS approach as a paracrine factor that is secreted by aortic and BM-MSCs, but in particularly high amounts by AoMSCs. This corroborates the general view that engraftment in the lung is currently not considered the main mechanism by which MSCs repair a diseased lung tissue (36,78). Consistently we detected only a few, preferably single donor cells in WTI lung sections while circulating enhanced green fluorescent protein [EGFP(+)] MSCs could be detected in peripheral blood even 25 weeks after transplantation, supporting the idea that tissue protection is due to paracrine signaling (44).…”
Section: Murine Wt Bm (Xrt/bm) Cells From C57bl/6 Donor Mice Into Thesupporting
confidence: 89%
“…MSCs were first identified in the bone marrow in 1976 (24) and have since been shown to express a broad spectrum of secreted molecules, including interferon (IFN)-γ, interleukin (IL)-1β, IL-6, IL-10, transforming growth factor (TGF)-β1, vascular endothelial growth factor (VEGF), stromal derived factor (SDF)-1, HGF, KGF, prostaglandin PGE2, amongst others (17,18). Through the action of these soluble mediators, BM-MSCs have been shown to modulate the activation, proliferation, and downstream effects of inflammatory and immune cells in both the innate and adaptive immune systems; including neutrophils, macrophages and lymphocytes (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the paracrine factors of MSCs have anti-apoptotic effects in vitro on cardiac cells (27,28), pancreatic β cells (29) and hepatocytes (19). BM-MSCs are known to produce several epithelial specific growth factors, including HGF and KGF (17,18), which have been proven to initiate a variety of biological responses including migration, proliferation, and morpho genesis in AECs (30)(31)(32)(33). Therefore it can be speculated that the protective roles of MSC-CM on AECs may be associated with the epithelial specific growth factors secreted by BM-MSCs and the synergistic effects of these factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9][10] For example, stem cells and regenerative medicine may off er solutions for disorders as diverse as acute lung injury, ARDS, idiopathic pulmonary fi brosis, COPD, genetic disorders (eg, cystic fi brosis and sickle cell disease), and reactive airway disease. [11][12][13][14] Translating stem cell-based therapies for the respiratory tract faces a number of hurdles, including ensuring safety and optimizing routes of delivery and dosage, but excitement abounds. 15 Th e clinical use of stem cell-based therapies is not just theoretical.…”
Section: Regenerative Medicine In Chest Medicinementioning
confidence: 99%